Murine CMV Expressing the High Affinity NKG2D Ligand MULT-1: A Model for the Development of Cytomegalovirus-Based Vaccines - Hiršl, Lea; Brizić, Ilija; Jenuš, Tina; Juranić Lisnić, Vanda; Reichel, Johanna Julia; Jurković, Slaven; Krmpotić, Astrid; Jonjić, Stipan (Frontiers in Immunology, 2018)
The development of a vaccine against human cytomegalovirus (CMV) has been a subject of long-term medical interest. The research during recent years identified CMV as an attractive vaccine vector against infectious diseases and tumors. The immune response to CMV persists over a lifetime and its unique feature is the inflationary T cell response to certain viral epitopes. CMV encodes numerous genes involved in immunoevasion, which are non-essential for virus growth in vitro. The deletion of those genes results in virus attenuation in vivo, which enables us to dramatically manipulate its virulence and the immune response. We have previously shown that the murine CMV (MCMV) expressing RAE-1γ, one of the cellular ligands for the NKG2D receptor, is highly attenuated in vivo but retains the ability to induce a strong CD8+ T cell response. Here we demonstrate that recombinant MCMV expressing high affinity NKG2D ligand MULT-1 (MULT-1MCMV) inserted in the place of its viral inhibitor is dramatically attenuated in vivo in an NK cell-dependent manner, both in immunocompetent adult mice and in immunologically immature newborns. MULT-1MCMV was more attenuated than the recombinant virus expressing RAE-1γ. Despite the drastic sensitivity to innate immune control, MULT-1MCMV induced an efficient CD8+ T cell response to viral and vectored antigens. By using in vitro assay, we showed that similar to RAE-1γMCMV, MULT-1 expressing virus provided strong priming of CD8+ T cells. Moreover, MULT-1MCMV was able to induce anti-viral antibodies, which after passing the transplacental barrier protect offspring of immunized mothers from challenge infection. Altogether, this study further supports the concept that CMV expressing NKG2D ligand possesses excellent characteristics to serve as a vaccine or vaccine vector.